1. \( \begin{aligned} 2 x-4 y & =-2 \\ -6 x+4 y & =-14\end{aligned} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve this system of equations, we can use the substitution or elimination method. Here, we can add both equations to eliminate one variable. Adding them gives: \[ (2x - 6x) + (-4y + 4y) = -2 - 14 \] This simplifies to: \[ -4x = -16 \quad \implies \quad x = 4 \] Now substitute \( x = 4 \) back into one of the original equations, say \( 2x - 4y = -2 \): \[ 2(4) - 4y = -2 \quad \implies \quad 8 - 4y = -2 \quad \implies \quad -4y = -2 - 8 \quad \implies \quad -4y = -10 \quad \implies \quad y = \frac{10}{4} = 2.5 \] Thus, the solution is \( x = 4 \) and \( y = 2.5 \). But let's not forget to check our work! Plugging \( x = 4 \) and \( y = 2.5 \) back into the second equation, \[ -6(4) + 4(2.5) = -14 \quad \implies \quad -24 + 10 = -14 \] Since both equations hold true, our solution is verified: \( (x, y) = (4, 2.5) \).